Waste Bank as a Waste Management Solution in Lawang Kajang Village, Timpah District, Kapuas Regency - Kosdamika, Yuhandra Conli; Gustina, Novia; Debi, Puspita Dewi; Septiana, Septiana; Wijaya, Ardi Anjungie Wahyu; Nehemia, Andika; Antie, Santri; Mariana, Mariana; Tania, Tania; Ezha, Vira; Jayanti, Lia Dwi; Lestaria, Farmingga; Prasetiawati, Prasetiawati (Pengabdian: Jurnal Abdimas, 2024)
Changes in consumption patterns have resulted in an increase in the volume, types and characteristics of diverse waste, This makes waste the center of attention and becomes a national problem so that its management needs to be carried out comprehensively so that it can provide benefits both economically, health and safety for the environment, and can change the life patterns of the people of Lawang Kajang village. This research is qualitative in nature and aims to analyze and describe the patterns of community life in Lawang Kajang Village, Timpah District, Kapuas Regency regarding the final processing of household waste. In the research carried out by IAKN Palangka Raya Regular KKN participants, several village officials and administrators were involved who were used as data sources. And information or data collection is carried out using interview techniques. So based on the information obtained, the people in Lawang Kajang Village still do not understand how to process waste, especially waste originating from households, there is a lot of rubbish scattered in the bushes next to community settlements, which shows the lack or lack of facilities and infrastructure, namely places village waste disposal. So starting from the problems that occurred at the KKN location, the IAKN Palangka Raya Group 1 Regular KKN team took the initiative to build a rubbish bin which was used as the main disposal site (TPSU) which was able to accommodate the entire waste while it was processed or processed to the final stage.